New results in G-best approximation in G-metric spaces - Dehghan, Nezhad A.; Mazaheri, H. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
The purpose of this paper is to introduce and discuss the concepts of G-best approximation and a_0 -orthogonality in the theory of G-metric spaces. We consider the relationship between these concepts and the dual X and obtain some results on subsets of G-metric spaces similar to normed spaces.